Danhong Injection and Trimetazidine Protect Cardiomyocytes and Enhance Calcium Handling after Myocardial Infarction - Zhang, Jingjing (Evid Based Complement Alternat Med, 2021)
Myocardial infarction (MI) is one of the leading causes of death worldwide. However, there is no effective treatment for MI. In this study, trimetazidine (TMZ) and Danhong injection (DHI), representing western medicine and traditional Chinese medicine for MI, were used as tools to identify vital processes in alleviating MI injury. Administration of DHI and TMZ obviously decreased myocardial infarct size, improved ultrasonic heart function, and reduced creatine kinase (CK), lactate dehydrogenase (LDH), and glutamic oxaloacetic transaminase (AST) levels after MI. RNA-seq results indicated calcium ion handling and negative regulation of apoptotic process were vital processes and DHI and TMZ obviously reduced the expression of CaMK II and inhibited cleaved caspase-3 and Bax. Furthermore, DHI and TMZ increased p-S16-PLB, p-S16T17-PLB, CACNA1C, p-RyR2, and p-PKA expression but did not affect SERCA2a expression. In addition to the enhancement of cardiac myocyte shortening amplitude, maximum shortening velocity, and calcium transients, DHI and TMZ increased sarcoplasmic reticulum calcium content and enhanced SERCA2a calcium uptake capability by upregulating the phosphorylation of PLB but did not affect calcium exclusion by NCX. In conclusion, DHI and TMZ protect against MI through inhibiting apoptosis by downregulating CaMKII pathway and enhancing cardiac myocyte contractile functions possibly through the PKA signaling pathway.